ANALISIS PENERAPAN DEEP LEARNING DALAM MODUL AJAR: TINJAUAN PUSTAKA - Suci Rahma Yuni; Yulia Rahmi; Adi Hidayat; Darul Ilmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The urgency of this research lies in the importance of implementing deep learning as a strategy to improve the quality of education and shape 21st-century competencies. These competencies include character building, critical thinking skills, creativity, collaboration, communication, and civic awareness. The deep learning approach offers learning that focuses on conceptual understanding, the integration of theoretical and applied knowledge, and the application of concepts in real-world contexts. The Deep Learning method and its application in the creation of teaching modules enable teachers to integrate the principles of mindful, meaningful, and enjoyable learning. This research uses a literature review method by analyzing various relevant literature sources to explore the challenges and opportunities in implementing deep learning in elementary schools. The results show that despite obstacles in terms of teacher readiness and educational infrastructure, the implementation of deep learning can increase student engagement, strengthen material understanding, and encourage the formation of critical and creative thinking patterns. Furthermore, this approach can be supported through ongoing teacher training, the application of educational technology, and flexible and innovative policies. With collaboration between educators, educational institutions, and other stakeholders, deep learning can become a catalyst for a more adaptive and relevant educational transformation. Therefore, structured steps are needed to overcome existing obstacles and maximize the potential of in-depth learning to create competent graduates who are ready to face global competition